Biblical spirituality: an "other" reading (allègoria) - Kees Waaijman (Acta Theologica)
This article discusses the communicative dimension and dialogical dynamic of a text, in order to illuminate the relationship of Biblical Spirituality with the Bible. From a pragmatic perspective on the polar tension between author, text and reader, the article reflects on the action of the author-text on the reader, and the action of the reader in relation to the text, as two strategies of reading. The article illustrates these two strategies in terms of seven paradigms. It points out how the essence of pragmatics lies in the fact that the polar tension does not allow for indifference on the reader’s part. Thus, a dialogical process is involved. The transition from an awareness of differences in respect of contents to dialogical non-indifference is crucial for Biblical Spirituality, because it marks the progression from a “meditative” way of reading, which is directed towards content (literary history), to an “orative” or prayerful way of reading, which is concerned with the God-human process of transformation.